Estudo comparativo do efeito de detergentes enzimático e alcalino na corrosão de instrumental cirúrgico fabricado com aço inoxidável AISI 304L, 316L e 420 - Caio César Freitas Xavier (2022)
Metallic instruments made of stainless steel are used both for surgical procedures and for manufacturing medical devices. Both uses require a high level of cleaning and sterilization, and these items, therefore, undergo recurrent cleaning cycles using water and detergents, which may have different types and mechanisms to carry out the cleaning. And like all steel, the items are also subject to oxidation, which can be accelerated when there is an attack on the passive layer formed by the oxides present in stainless steel. This study aims to test two types of detergents, alkaline and enzymatic, with different properties such as pH of 9.0 to the first and 12.3 to the latter, and comparing their effects on corrosion resistance of AISI 304L, 316L and 420 stainless steels, used in the manufacturing of surgical instruments. By using Electrochemical Impedance Spectroscopy and potentiodynamic polarization tests, the AISI 304L stainless steel was found to have the best behavior among the three stainless steels tested, having the highest corrosion resistance in enzymatic medium. The AISI 316L steel had an intermediate behavior in enzymatic medium, and lower impedance when immersed in alkaline detergent, while the AISI 420 steel showed better results in alkaline medium when compared to enzymatic solution, reinforcing the need to choose the cleaning agent based on the stainless steel used, and in other conditions specific for each application.